Comparison of the antimicrobial efficacy of povidone-iodine-alcohol versus chlorhexidine-alcohol for surgical skin preparation on the aerobic and anaerobic skin flora of the shoulder region - Dörfel, Dorothea Daniela; Maiwald, Matthias; Daeschlein, Georg; Müller, Gerald; Hudek, Robert; Assadian, Ojan; Kampf, Günter; Kohlmann, Thomas; Harnoß, Julian-Camill; Kramer, Axel (Antimicrobial resistance and infection control, 2021)
Cutibacterium acnes is part of the anaerobic skin microbiome and resides in deeper skin layers. The organism is an agent of surgical site infections (SSI) in shoulder surgery. We hypothesized that prolonged skin preparation with an agent that penetrates deeply into the skin would be beneficial. Thus, we compared two classes of antiseptics, each combined with alcohol, each applied with two different contact times.